HISTOCHEMICAL INVESTIGATION OF GLYCOSAMINOGLYCANS OF THE MANDIBULAR ALVEOLAR PROCESS IN PHARMACOLOGICAL CORRECTION OF EXPERIMENTAL OSTEOPOROSIS AND PERIODONTITIS - O.I. Hodovana (Ukrainian Medical Stomatological Academy, 2018)
The current issueof this study is to search for the ways and elaboration of treatment schemes, which include pharmacological means, capable of inhibiting processes of bone tissue resorption, and which show periodontium-protective action. The aim of the research was histological and histochemical investigation of the mandibular bone tissue, caudal vertebra and femur of rats with prior modeling of systemic osteoporosis and periodontitis. Influence of osteotropic medications, "Osteogenon" "Vitrum®Osteomag", "Bivalos®" and "Teraflex®" on bone tissue was studied in comparative aspect. Glycogen and basic glycosaminoglycans (GAGs) were identified by means of PAS- reaction after MacManus, and acid GAGs - by alcian blue after Stidman. It has been established that the action of different osteotropic medicines has various influences on skeletal bones. In the norm (group №1) low level of PAS-positive substances in skeletal bones showed absence of signs of the inflammatory process. Slight deposit of basic GAGs (7.94%) with the absence of acid GAGs, most likely, was the evidence of a normal course of bone tissue modeling. In pathological process - systemic osteoporosis and periodontitis in group №2 in impairment of organization of all structural components of bone tissue, particularly modifications of compact and spongy substance, the level of basic GAGs drastically increased (71.74%) and slight amount of reserved acid GAGs (15.49%) appeared in all examined bones as a body's reaction to damage. Having analyzed bones of group №3, animals of which received "Osteogenon", the highest level of acid GAGs, involved in tissue reparation, was detected in femurs (67.34%). At the same time, the lowest level was observed in mandibular bone (20.27%). Unlike group №3, which received "Osteogenon", use of medication "Vitrum®Osteomag" by animals of group №4 resulted in low concentration of acid GAGs in femurs (15.54%), while this medication potentiated their significant growth in caudal vertebrae (69.49%). In jawbones basic GAGs dominated (64.35%) over low amount of acid GAGs (15.85%). In animals from group №5, which used medication "Bivalos®", simultaneous increase in amount of basic (73.72%) and acid (58.35%) GAGs was observed in bone tissue of the vertebrae. Femur and mandible showed low amount of acid GAGs (15.70%) and moderate amount of basic GAGs (60.64%). In 2 months' treatment with this medication, numerous foci of resorption in the form of oval newly formed lacunae were seen in compact bone of the alveolar process in the mandible. Trabeculae of spongy bone were thin and deformed. In group №6, animals of which received "Teraflex®" (glucosamine hydrochloride and sodium chondroitin sulfate), the highest level of acid GAGs (75.47%) was observed in bone tissue of vertebrae, while in femur it was 51.26%. Unlike previous subgroups, the highest level of acid GAGs (59.76%) was revealed in jawbones of group №6 in accelerated course of regeneration processes, which proved the expediency and high efficacy of medication "Teraflex®", used for animals with modeled periodontitis and systemic osteoporosis. Among other peculiarities of conducted pharmacological correction of pathological process, it was established that appearance of micro fissures in bone tissue of the mandible, femur and vertebrae was observed in examined samples of animals, which received "Osteogenon" "Vitrum®Osteomag", "Bivalos®" and "Teraflex®". Thus, the obtained data enable to recommend medication on the basis of GAG "Teraflex®" for inclusion to scheme of complex treatment of patients with periodontitis with various degrees of severity in systemic osteoporosis/osteopenia.